Membaca Fenomena Menguatnya Perayaan â€œIslamisasiâ€ di Indonesia Pasca Reformasi - Jayanto, Dian Dwi (Sekolah Pascasarjana UGM, 2020)
The strengthening of Islamization (Islamisasi) or the revival of religious awakening in the post-reform Indonesia has become an appealing topic to be studied by social scientists. Islamization, in this study, is not defined in terms of the discourse of religious political relations (such as relations of state and religion), but refers to the existence of social religious expressions which are marked by considerable exploration to form a new meaning of Islam (Islamization) which involves various elements, especially capitalism and modernity. This paper provides an overview of how social scientists see the phenomenon of Islamization in the post-reform Indonesia. This overview is important in order to discuss the viewpoints or better known as